Obstacles in combating multidrug resistant tuberculosis in pediatric patients: a scope review - Letícia Baltar Sobreira; Paula de Souza Silva Freitas; Luciana de Cassia Nunes Nascimento; Anne Caroline Barbosa Cerqueira Vieira; Carolina Maia Martins Sales; Alicia de Oliveira Pacheco; Lucas Dalvi Armond Rezende (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to identify the scientific evidence on excessively resistant and multidrug resistant tuberculosis in pediatric patients. Methods: this is a scope review of the literature, with a guiding question: "What is the scientific evidence on multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis in pediatric patients?". The research used the descriptors: "extensively drug-resistant tuberculosis" OR "multidrug-resistant tuberculosis" AND "pediatrics". The research was carried out in a double-blind manner in the following databases of the Medical Literature Analysis and Retrieval System Online, Regional Office for the Western Pacific's Institutional Repository for Information Sharing, Embase/Elsevier and International Clinical Trials Registry Platform, with a temporal cut-off from 2011 to 2021, sending a final synthesized sample of 18 articles, which evaluated the methodological content through the level of evidence. Results: the results show the lack of research with a high level of evidence related to MDR-TB in children, the lack of adequate dosage of second-line drugs for the pediatric population and the importance of drug sensitivity testing for the cases of treatment Conclusions: it was identified that the obstacles to MDR-TB treatment were concentrated in the lack of detailed protocols, safe drug dosages with a low side effect, and mainly in the social health determinants and disease process involving MDR-TB.